Species diversity of benthic diatoms and its relation to environmental variables in Ton Ngachang Waterfall, Songkhla province - V. Dummee (2018)
The species diversity of benthic diatoms and its relation to environmental variables were studied in Ton Ngachang Waterfall, Songkhla province. Epilithic and epipsammic diatoms were sampled at 5 stations from upstream (station 1, 2 and 3) to downstream (station 4 and 5) in summer (April 2004 and February 2005), early rainy season (June and August 2004) and rainy season (November and December 2004). A total number of 15 genera, 49 species and 8 families in order Pennales were found. Achnanthes was the dominant genus throughout the study period with 8 species. A principal components analysis (PCA) on relative abundance revealed that Achnanthes minutissima Kützing and A. lanceolata (Brebission) Grunow were the most abundant species of epilithic diatoms and epipsammic diatoms respectively, whereas species richness on both substrata were not significant different (P>0.05). Analysis of variance (ANOVA) indicated that the numbers of benthic diatom species between upstream and downstream were not significant different (P>0.05), while there was statistical significance (P<0.05) among the seasons in epilithic diatoms. Multivariate analysis of variance (MANOVA) on physico-chemical factors showed that nitrate, ortho-phosphate, silicate, BOD, conductivity and TSS were significant different (P>0.05) between seasons. Canonical correspondence analysis (CCA) ordination indicated that nitrate, silicate, BOD, pH, conductivity, temperature and velocity were correlated with the benthic diatom abundance.